On the monoterpene emission under heat stress and on the increased thermotolerance of leaves of Quercus ilex L. fumigated with selected monoterpenes - Loreto, F.; Förster, A.; Dürr, M.; Csiky, O.; Seufert, G. (Plant, Cell & Environment, 1998)
Leaves of the monoterpene emitter Quercus ilex were exposed to a temperature ramp with 5 °C steps from 30 to 55 °C while maintained under conditions in which endogenous emission of monoterpenes was allowed or suppressed, or under fumigation with selected exogenous monoterpenes. Fumigation with monoterpenes reduced the decline of photosynthesis, photorespiration and monoterpene emission found in non-fumigated leaves exposed to high temperatures. It also substantially increased respiration when photosynthesis and photorespiration were inhibited by low O2 and CO2-free air. These results indicate that, as previously reported for isoprene, monoterpenes may help plants cope with heat stress. Monoterpenes may enhance membrane stability, thus providing a rather non-specific protection of photosynthetic and respiratory processes. Monoterpene emission was maximal at a temperature of 35 °C and was inhibited at higher temperatures. This is likely to be the result of the temperature dependency of the enzymes involved in monoterpene synthesis. In contrast to other monoterpenes, cis- and trans-β-ocimene did not respond to exposure to high temperatures. Cis-β-ocimene also did not respond to low O2 or to fumigation. These results indicate that cis and trans-β-ocimene may have a different pathway of formation that probably does not involve enzymatic synthesis.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: monoterpene emission; monoterpene fumigation; photosynthesis; Quercus ilex; respiration; thermotolerance